Prospects for building resilience to external shocks and mitigating their impact on trade and development (UN New YorkUS, 2013)
Examines the statistical tools (in particular those related to international trade) that are needed to improve the understanding of external shocks and their economic impact, and help design appropriate policy responses.
Keywords: ECONOMIC POLICY